PENGELOLAAN JARINGAN DOKUMENTASI DAN INFORMASI HUKUM DALAM MENUNJANG INFORMASI PELAYANAN PUBLIK PADA KOMISI PEMILIHAN UMUM PROVINSI KALIMANTAN TENGAH: The management of Law Documentation and Information Networking in Providing Public Services at the Commission of Public Election of Central Kalimantan Province - Desia Asrina Wulandari; Muhamad Yusuf; Nurhasanah (Pencerah Publik, 2023)
The aim of this research is to describe how the management of Law Documentation and Information Networking (JDIH) provide public services at the Commission of Public Election (KPU) of Central Kalimantan Province for supporting community public services in information and law products This research applies qualitative approach with descriptive method. The data collection techniques were: 1) interview, 2) observation, and 3) documentation. The results show that the management of JDIH at KPU of Central Kalimantan Province in providing information/ law products has not been optimal yet. Developing quantity and quality of human resources is strongly needed in order to have the jobs finish effectively in accordance with the Standard Operational Procedures (SOP). It can be optimally by adding the quantity of personnel with suitable educational background/ skills and training. Adding appropriate infrastructures, especially networking/ internet system and application system, also special working rooms and library for JDIH will support the existence of law data/ information of KPU for the public. Public as the users of JDIH website will be helped by the existence of JDIH at KPU Central Kalimantan Province for finding law data/ information easily, effectively that is suitable with the aspects of prime public services.